Recommendations and examination protocols for pre-purchase examination in South American camelids - Wittek, Thomas; Kröll, Bodo; Rudovsky, Annett; Franz, Sonja; Wagner, Henrik (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2025)
This article provides information and recommendations for the pre-purchase physical and laboratory examinations of South American camelids (SAC). It is strongly recommended to have a written contract between the potential buyer and the veterinarian before the examination detailing its form and focus including any tests. The pre-purchase examination subsequently leads to the production of a report describing the animal’s signalment, history and the results of the examinations following the contract description. It may be necessary to involve the seller in this contract (e. g. if the animal is to be subjected to an examination that may put it at risk).SACs are used for various purposes (e. g. wool, tourism, animal assisted therapy) and the purpose desired by the purchaser will determine the scope of the pre-purchase examination. To allow this, a modular system is proposed so that, in addition to the general examinations (physical and laboratory) the appropriate clinical and laboratory findings can be compiled from various “special” examinations. Thus, in addition to the obligatory general physical and laboratory diagnostic examination, special examination protocols e. g. skin examination for animals that are primarily used for fleece production, full scale orthopedic examination in animals that will be used for hiking or examination for infectious diseases in animals that have close contact with humans can be chosen as part of the pre-purchase examination. The last mentioned may be of general importance depending on the signalment and history. Diagnoses can then be made in accordance with the proposed main use(s) of the animal.When taking on the assignment of a pre-purchase examination, the veterinarians have to guarantee that they possess the appropriate skills and experience and that the required equipment and laboratory access is available. Finally, the veterinarians must document the findings precisely in the final report and maintain absolute confidentiality.The authors of the present article have compiled recommendations on pre-purchase examinations and developed examination protocols. These protocols are made available for download as PDF files in German and English (https://www.vetmeduni.ac.at./ankaufsuntersuchung-neuweltkamele).
Keywords: Pre-purchase examination; llama; alpaca; South American camelids